Broad-Band Integrated Optical Electric Field Sensor Using Reflection Mach-Zehnder Waveguide Modulator. Issue 4 (3rd September 2017) - Zhang, Jiahong; Zhao, Zhengang; Li, Chuan; Li, Yingna
ABSTRACT: A lithium niobate (LiNbO3 ) broad-band photonic sensor using reflection-type Mach-Zehnder optical waveguide modulator has been designed, fabricated, and experimentally demonstrated. The bare chip size of the sensor is microminiaturized as small as 20×5×0.5 mm 3 . The sensor has a wide band frequency response from 10 kHz to 20 GHz with variation less than ± 5 dB. The sensor system shows better linear characteristic from 100 mV/m to 700 V/m, and the sensitivity is 33 mV/m. Besides, the nanosecond EMP with intensity of 30 kV/m has been measured in the time domain.